PROSES KERJA DIGESTER DAN SISTEM PERAWATAN PADA PT.PERKEBUNAN NUSANTARA IV PKS DOLOK ILIR - adusman silalahi, adrianjhonatan; SILALAHI, ANDRIAN JONATHAN (Jurnal Penelitian Teknik Dan Sumberdaya Perairan, 2025)
Field work practice (PKL) is an academic activity that aims to provide real experience to students in understanding the knowledge gained during lectures. The implementation of this PKL was carried out at PTPN IV DOLOK ILIR with a focus on the work process and maintenance of the digester. which functions to crush oil palm fruit bunches before the pressing process. The performance of the digester greatly affects the efficiency of oil separation and the quality of the resulting crude palm oil (CPO). This Field Work Practice (PKL) activity aims to determine the digester's working system and the maintenance system applied to maintain optimal machine performance. The methods used in this study were direct observation in the field, interviews with operators and technicians, and documentation studies of operational procedures and machine maintenance schedules. The results of the observations showed that the digester's work process includes filling the bunches, heating using steam at a temperature of ±90–95°C, and the stirring process using a stirring arm to soften the fruit flesh. The maintenance system implemented includes preventive maintenance such as routine inspection of the stirring blade, bearing lubrication, checking the heating system, and cleaning the inside of the digester. Implementing scheduled maintenance in accordance with standard operating procedures has been proven to reduce the potential for machine damage and support the smooth running of the CPO production process.